THE ROLE OF THE GENERAL TUNISIAN LABOUR UNION (UGTT) IN TUNISIA REVOLUTION 2010-2011 - Santika Nindya Sari (HI 15 UMY 058, 2015)
*58 The General Tunisian Labor Union (UGTT) is a strongest labour union in Tunisia during revolution in 2010 until 2011. UGTT as the key of revolutionary group play a key role in the process of Tunisia Revolution which was started their act in supporting anti-Ben Ali protests. The Tunisian General Labour Union is an independent organization that focuses on trade union organization and national democracy for all organizations where they gain legitimacy and strength that come from the union. The General Tunisian Labor Union (UGTT) is a symbol of their country’s struggle for independence, human rights and dignity. In the context of Internationla relations, UGTT is a part of Civil Society Organizations. Tunisia have strong civil society which all of labor n Tunisia was involved in revolution. This article aims to analyze and elaborate the General Tunisian Labor Union (UGTT) roles in Tunisian revolution during 2010 until 2011. UGTT played pivotal role as key revolutionary actor to lead social movement by using propaganda method. Author argues that UGTT in doing its activities was using card stacking and bandwagon techniques of propaganda. This article also conclude that civil society might be potential actor for an organization to launch their political interest through effective propaganda method. UGTT had become the only actor in the Tunisian revolution which gained Tunisian trust to lead them in the Tunisian revolution. The organizational strength was indicated by the number of members involved in the organization to influence the Tunisian society. Such discussion above has lead to the idea that propaganda is an effective way which conducted by the UGTT in Tunisia's revolution. UGTT as a key revolutionary group had helped people to make the revolution. Civil society was become the approach for an organization to launch their interests.